Wind Erosion of Cropland in the Northwestern Tarim Basin. Issue 3 (24th June 2016) - Zheng, Zehao; Sharratt, Brenton; Feng, Gary; Li, Xinhu; Pi, Huawei
Abstract : Core Ideas: The Tarim Basin is a major source of windblown dust in Asia and China. No studies have previously documented wind erosion from cropland in Tarim Basin. Wind erosion was measured from an irrigated cotton field and red date orchard. Wind erosion from cropland is lower than from China's deserts. Management practices must be developed to control wind erosion in Tarim Basin. The Aksu region within the Tarim Basin is a major source of windblown dust in China due to the arid climate and vast areas under intensive irrigated crop production. Despite the importance of crop production to human subsistence and the local economy, little is known about the amount of soil eroded by wind from agricultural lands in the region. Passive aeolian sediment collectors were used to measure soil loss from an irrigated cotton ( Gossypium spp.) field and red date ( Ziziphus jujuba Mill.) orchard in the Aksu Oasis during high wind events in 2012 and 2013. Mass of sediment trapped by the collectors was best described as a power function of height above the surface in the cotton field and red date orchard. Soil loss from the cotton field ranged from 0 to 142 g m −2, whereas soil loss from the red date orchard ranged from 0 to 71 g m −2 for single‐ or multiple‐day high wind events. Total soil loss from the cotton field and red date orchard, for the high wind events observed in this study, was 130 and 96 g m −2, respectively, in 2012 and 305 and 165 g m −2, respectively, in 2013. Soil loss was similar to that reported from agricultural lands in other regions of the world. Although soil loss is relatively small compared with the Gobi Desert in China, poor air quality in the Tarim Basin necessitates identifying crop and soil management practices for reducing windblown dust and conserving the soil resource.